Enhancing Donation-Based Crowdfunding with Togaf & AI: Sustainability Case Study at Foundation XYZ - Muhammad Teguh Prasetyo; Erick Dazki (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Crowdfunding has emerged as a crucial mechanism for expanding financial accessibility, particularly for projects focused on sustainability. However, the success of foundation-based crowdfunding largely depends on trust and transparency. This study aims to investigate the role of these factors in influencing donor confidence and campaign success. Utilizing a mixed-method approach, the research combines qualitative and quantitative data analysis. The study was conducted on active crowdfunding campaigns within sustainability-focused foundations, employing surveys, interviews, and platform data analytics to assess stakeholder engagement, financial transparency, and campaign effectiveness. The findings reveal that transparent fund management significantly impacts donor trust, with campaigns demonstrating clear financial accountability attracting more sustained contributions. Additionally, the study identifies the importance of effective communication and measurable impact reporting in fostering a supportive crowdfunding ecosystem. The research provides actionable recommendations for foundation-based giving organizations and sustainable entrepreneurs to strengthen transparency and stakeholder involvement, ultimately enhancing donor confidence and community support for sustainability initiatives.